RTOS acceleration in an MPSoC with reconfigurable hardware. (July 2016) - Zaykov, Pavel G.; Kuzmanov, Georgi; Molnos, Anca; Goossens, Kees
Abstract: In this paper, we address the problem of improving the performance of real-time embedded Multiprocessor System-on-Chip (MPSoC). Such MPSoCs often execute applications composed of multiple tasks. The tasks on each processor are scheduled by a Real-Time Operating System (RTOS) instance. To improve performance, we reduce the Worst Case Execution Time (WCET) of the RTOS by new processor-coprocessor execution models using reconfigurable hardware. Furthermore, we integrate the proposed contributions on an MPSoC platform, where the processor-coprocessor execution models are applied on three reconfigurable coprocessors - Hardware Task-Status Manager (HWTSM), Thread Interrupt State Controller (TISC), and Remote Slack Manager (RSM). As a case study, we investigate the HWTSM, which determines the execution eligibility of tasks. The experimental results suggest overall system improvement up to 13.3% with the help of the HWTSM. Moreover, the TISC can boost further the performance and RSM can significantly reduce the energy consumption.